Entrepreneurship Practice through Wholesale and Retail Outlets and Pharmaceutical Practice among Companies in Lagos State, Nigeria (International Journal of Scientific Research and Management (IJSRM), 2024)
The research examined entrepreneurship and pharmaceutical practices among companies in Lagos State, Nigeria with a focus on wholesale and retail outlets. The choice of Lagos is precipitated on the fact that it commanded large percentage of commercial activities in Nigeria and the study showed the role of entrepreneurship in improving the logistics of the wholesale and retail pharmaceutical companies in Lagos State, Nigeria. The study employed the quantitative research method. This was to evaluate the link between logistics entrepreneurship and pharmaceutical performance. The findings showed that entrepreneurship improves the logistics of retail and wholesale pharmaceutical practice in Lagos State, Nigeria. The findings also confirmed that entrepreneurship is important on the performance of pharmaceutical companies in Lagos State, Nigeria. There was great evidence that entrepreneurship orientation is needed in the pharmaceutical sector. The research concluded that introduction of entrepreneurship logistics through wholesale and retail outlets would enhance the overall performance of pharmaceutical companies in Lagos State, Nigeria. It therefore recommended that Pharmaceutical retail and wholesale companies should pay a good attention to their logistics management by employing the critical elements of entrepreneurship which include creation, organization, administration and distribution, under a conducive regulatory environment and also special route system should be created in major Nigerian cities especially Lagos, reserved only for medical and pharmaceutical conveyances.